2018
DOI: 10.1038/s41598-018-21447-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure in spiking patterns of ganglion cells defines perceptual thresholds in rodents with subretinal prosthesis

Abstract: Subretinal prostheses are designed to restore sight in patients blinded by retinal degeneration using electrical stimulation of the inner retinal neurons. To relate retinal output to perception, we studied behavioral thresholds in blind rats with photovoltaic subretinal prostheses stimulated by full-field pulsed illumination at 20 Hz, and measured retinal ganglion cell (RGC) responses to similar stimuli ex-vivo. Behaviorally, rats exhibited startling response to changes in brightness, with an average contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…Figures 2c-e show example receptive fields and time courses (spiketriggered average, STA) for natural visual response, electrical stimulation of the healthy retina, and electrical stimulation of RCS retina, respectively. Electrically stimulated cells generally have faster, but weaker STAs, similar to previous observations (8,11).…”
Section: Spike Sortingsupporting
confidence: 88%
See 1 more Smart Citation
“…Figures 2c-e show example receptive fields and time courses (spiketriggered average, STA) for natural visual response, electrical stimulation of the healthy retina, and electrical stimulation of RCS retina, respectively. Electrically stimulated cells generally have faster, but weaker STAs, similar to previous observations (8,11).…”
Section: Spike Sortingsupporting
confidence: 88%
“…This may be explained by stimulation of rod bipolar cells, which feed into the ON and OFF cone pathways via amacrine cells. Contrast sensitivity of prosthetic vision in rats appears to be about 5 times lower than natural (11), which could be partially compensated by image processing prior to projection into the eye. Clinical trial demonstrated that patients correctly perceive various patterns of lines and letters, demonstrating monochromatic shaped vision with resolution closely matching the pixel size (100 μm in the first trial) (7).…”
Section: Introductionmentioning
confidence: 91%
“…Preserved features include flicker fusion at high frequencies, 82 antagonistic center-surround organization 83 and nonlinear summation of subunits in receptive fields, 82 as well as ON and OFF responses. 84 Another theoretical advantage of the subretinal placement is that it provides close and stable proximity of electrodes to the target neurons. However, implantation in the subretinal space can be more difficult than the epiretinal approach, and removal of the implant is also more challenging.…”
Section: Retinal Prosthetic Devicesmentioning
confidence: 99%
“…Retinal and subretinal inorganic prostheses were developed to restore sight in patients blinded by retinal degeneration by stimulating the inner retinal neurons using 3D pillar electrodes (Figure 1D ) which enhance the cell-chip coupling and the integration the implant in the target tissue (Mathieson et al, 2012 ; Flores et al, 2018 ). In a recent work done by Ho et al ( 2018a ) a photodiode array made of boron-doped silicon-on-insulator (SOI) wafers was used to perform in vivo and in vitro measurements, in which the retina is placed between the recording array (ganglion cell side) and the photodiode array (photoreceptor side). In a recent work, transparent extracellular microelectrode arrays (MEA) were used to characterize the spatial and temporal response properties of retinal ganglion cells (RGCs) to photovoltaic stimulation in the healthy and degenerate rat retina (Ho et al, 2018b ).…”
Section: Electrogenic Cellsmentioning
confidence: 99%